Pemanfaatan aplikasi tiktok terhadap peningkatan penjualan produk kreatif - Karlin, Mochammad Karlin; Nurdiana, Ratna; Suryanto, Hadi (Journal of Creative Attitudes Culture, 2023)
Social media has a positive impact, namely making it easier to exchange information and making it easier to obtain online literature. Tiktok is a social networking application and music video platform from China which was launched in September 2016. This application is used by users to create their own short music videos. Welding at SMK Negeri 2 Lamongan in 2023. The hypothesis in this research is "H1: There is an influence of using the Tiktok application on increasing sales of creative products for Class XI students of welding techniques at SMK Negeri 2 Lamongan in 2022." "H0: There is no influence of using the Tiktok application on increasing sales of creative products for class XI students of welding engineering at SMK Negeri 2 Lamongan in 2022." The research method used, researchers used quantitative methods. The population and sample are Class XI Welding Engineering students at SMK Negeri 2 Lamongan in 2022, totaling 36 students. The results of using the TikTok application for class XI Welding Engineering students at SMK Negeri 2 Lamongan can be categorized as high after using the TikTok application. Sales of creative products for Class XI Welding Engineering students at SMK Negeri 2 Lamongan have increased after using the TikTok application. The use of the TikTok application to increase sales of creative products for class